(untitled) (Research, Society and Development, 2021)
The Psychiatric Reform was a historical process whose main objective was to ensure the humanization of care for people who experience psychological distress. This article searches the national literature, reflecting on the vicissitudes of the relational dimension of care, the constitution of RAPS as an instrument for promoting humanization in health, social inclusion and breaking all the stigma surrounding mental health. This study aims to reflect on the mental health care provided by the Psychosocial Health Care Network (RAPS). This is a theoretical essay that discusses mental health care from the perspective of the Psychiatric Reform, having as theoretical reference the ontological care, seen under the phenomenology according to Heidegger. The discussion about the theme occurs in two moments, reflecting on the role of care and the Psychiatric Reform in the articulation of mental health services. So, care involves a series of theoretical and practical principles that are necessary to offer a more humane assistance to health. Even in the face of setbacks and weaknesses faced by Brazilian Mental Health, professionals need to reflect and reframe the humanization of care in the context of mental health. Mental health professionals should always strive for assistance that is more based on valuing the individual, taking into account the user’s social, economic and cultural context.